Topics in the syntax of Qur'ānic Arabic - Kayam, O (2023)
Many features of Qurʾānic Arabic do not fit within the grammar of Classical Arabic as described by medieval grammarians. This calls for a specialised grammar of Qurʾānic Arabic, which should be composed based on a descriptive investigation of the Qurʾān as a self-contained corpus. Studies have lately been conducted on some aspects of the phonology, morphology and syntax of the language of the Qurʾān; however, the work – particularly in syntax – is far from complete. The present thesis seeks to contribute to the recent research of the grammar of Qurʾānic Arabic, especially its syntax. Each part systematically describes the linguistic feature around which it revolves. Emphasis is put on aspects that are unique to the Qurʾān, some of which have hitherto been unexplored in research, as opposed to extra-Qurʾānic Arabic.